Dynamic analysis of forklift truck using building block approach. (5th August 2014) - Suzuki, S.; Kawabata, Y.; Mori, N.; Kadokawa, Y.; Hasegawa, J.; Nishi, G.
The Building Block Approach is an improved concept in dynamic analysis of complex machinery. This method was applied to make a mathematical model of a forklift truck. Using this model, the dynamic response of the steering wheel caused by the engine vibration was analysed. Furthermore, this model predicted the effect of modifications to the steering components before they were implemented. The effect of these changes was confirmed by testing the modified truck.